2020
DOI: 10.26442/00403660.2020.12.200464
|View full text |Cite
|
Sign up to set email alerts
|

BCG, muramylpeptides, trained immunity (part I): linkages in the light of the COVID-19 pandemic

Abstract: It has long been known that Bacillus CalmetteGurin (BCG) vaccine provides nonspecific protection against many non-mycobacterial infections, which has been discussed in the last decade through the prism of the concept of trained immunity. Within the framework of this concept, a persistent increase in resistance to various pathogens, which occurs after an infectious disease or exposure to certain microbial agents, is associated with epigenetic reprogramming of innate immune cells and their bone marrow progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In sum, our findings demonstrate that exogenous administration of a host immunomodulatory transcription factor, YB-1, can boost in vivo B cell responses; moreover, short (12 h) pre-exposure to YB-1 was found to protect against acute lethal challenge with E. coli. independently of or in conjunction with its ligands GMDP/MDP, can influence cytokine secretion and offer significant protection not only against acute infections of outstanding topical interest (i.e., COVID [66]) but also against protracted infections such as those implicated in neurodegenerative diseases including AD and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, our findings demonstrate that exogenous administration of a host immunomodulatory transcription factor, YB-1, can boost in vivo B cell responses; moreover, short (12 h) pre-exposure to YB-1 was found to protect against acute lethal challenge with E. coli. independently of or in conjunction with its ligands GMDP/MDP, can influence cytokine secretion and offer significant protection not only against acute infections of outstanding topical interest (i.e., COVID [66]) but also against protracted infections such as those implicated in neurodegenerative diseases including AD and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies revealed that BCG immunization provides significant protection against viral infections by inducing trained immunity (28)(29)(30). In this direction, the potential benefits of BCG vaccination on protecting against COVID-19 have been actively postulated (18,20,(31)(32)(33)(34)(35)(36)(37). Martha et.…”
Section: Introductionmentioning
confidence: 99%